PUBLIC PERCEPTION OF ONLINE MONITORING SYSTEM INSTALLATION IN CILIWUNG RIVER - Yudo, Satmoko (BPPT)
Ciliwung River flows through the city center and passes through the village, dense housing and slums. So that the river is experiencing the most severe pollution mainly household waste water and industrial pollution compared with other rivers that flow in Jakarta. One of the efforts to control pollution of the river is by monitoring the water quality of the river. This monitoring should be carried out continuously online to analyze the quality of water entering or residing in the water bodies. To support the plan of installing online monitoring system of river water quality is necessary to know the perception of people who are in locations where the system installed. This is done with the aim to socialized the implementation plan and to determine the support and participation of the public in the vicinity. The results of this study show that the majority of the population supports the installation of technology online water quality monitoring in the Ciliwung River. With the hope that people can know directly how the conditions of Ciliwung River water quality.Key words: Ciliwung river, online monitoring of water quality technology, public perception